Influence of Age Difference on Decision-Making Styles and Accuracy (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study investigates how age differences influence decision-making styles and accuracy. A structured survey was conducted among 250 participants from different age groups, and a chi-square test was applied to examine the relationship between age and decision-making effectiveness. The results indicate that younger individuals tend to make faster yet riskier decisions, whereas older individuals rely more on systematic analysis. These findings contribute to understanding cognitive and behavioral variations in decision-making across different life stages.